Collagen XII mediated cellular and extracellular mechanisms in development, regeneration, and disease - Izu, Yayoi; Birk, David E. (Frontiers in Cell and Developmental Biology, 2023)
Collagen XII, a fibril-associated collagen with interrupted triple helices (FACIT), influences fibrillogenesis in numerous tissues. In addition to this extracellular function, collagen XII also directly regulates cellular function. Collagen XII is widely expressed in connective tissues, particularly tendons, ligaments, and the periodontium and periosteum, where it is enriched in the pericellular regions. Mutations in the collagen XII gene cause myopathic Ehlers-Danlos syndrome (mEDS), an early-onset disease characterized by overlapping connective tissue abnormalities and muscle weakness. Patients with mEDS exhibit delayed motor development, muscle weakness, joint laxity, hypermobility, joint contractures, and abnormal wound healing. An mEDS mouse model was generated by deletion of the Col12a1 gene, resulting in skeletal and muscle abnormalities with disorganized tissue structures and altered mechanical properties. Extracellularly, collagen XII interacts with collagen I fibrils and regulates collagen fibril spacing and assembly during fibrillogenesis. Evidence for the binding of collagen XII to other EDS-related molecules (e.g., decorin and tenascin X) suggests that disruption of ECM molecular interactions is one of the causes of connective tissue pathology in mEDS. Collagen XII also has been shown to influence cell behavior, such as cell shape and cell-cell communication, by providing physical connection between adjacent cells during tissue development and regeneration. The focus of this review is on the functions of collagen XII in development, regeneration, and disease.